Implementation of the motive of women friendship in British and Ukrainian modernism (based on the works of Virginia Woolf and Lesya Ukrainka) - Ніколайчук, Ірина Анатоліївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article deals with the problem of implementation of the motive of women friendship in works, as well as biographical and autobiographical materials (diaries and correspondence), of Virginia Woolf and Lesya Ukrainka as a key to self-identifying of female author in the aesthetics of modernism. The main points of analysis are: the role of the motive for the plot construction; its conceptual background; formal and stylistic features of its functioning of the text; and its connection with the personal biography of each of the women writers.